2011
DOI: 10.14712/18059694.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus in Primigravidae: a Mild Disease

Abstract: This prospective observational study was done to analyse the prevalence of gestational diabetes mellitus (GDM) among primigravidae and its outcome. All healthy primigravidae with singleton pregnancies were offered universal glucose tolerance testing between 16 and 28 weeks gestation. GDM and non GDM groups were managed according to hospital protocol. The antenatal features and pregnancy outcomes were analysed. Out of 616 primigravidae, 113 (18.34 %) were GDM with slightly older (27.9 ± 4.2 versus 26.32 ± 3.3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Of the 124 items found from the database and internet search, we included 15 publications in the qualitative analysis (Basri et al 2018;Gill et al 2012;Goh et al 2018;Hasbullah et al 2020;Idris et al 2009;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Kampan et al 2013;Logakodie et al 2018;Muniswaran et al 2017;Nordin et al 2006;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007. Two publications with low quality score were excluded (lack of information on the patient recruitment and diagnostic method) (Goh et al 2018;Muniswaran et al 2017).…”
Section: Search Resultsmentioning
confidence: 99%
“…Of the 124 items found from the database and internet search, we included 15 publications in the qualitative analysis (Basri et al 2018;Gill et al 2012;Goh et al 2018;Hasbullah et al 2020;Idris et al 2009;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Kampan et al 2013;Logakodie et al 2018;Muniswaran et al 2017;Nordin et al 2006;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007. Two publications with low quality score were excluded (lack of information on the patient recruitment and diagnostic method) (Goh et al 2018;Muniswaran et al 2017).…”
Section: Search Resultsmentioning
confidence: 99%
“…Women who are not diabetic or obese before pregnancy can develop insulin resistance due to changes in hormones or intestinal flora or weight gain during pregnancy, and the condition may even develop into GDM. Studies have shown that the incidence rate of GDM can be as high as 14% [ 45 ]. The composition changes of the intestinal flora during pregnancy may affect the metabolic function of the host.…”
Section: Discussionmentioning
confidence: 99%
“…The Hyperglycemia and Adverse Pregnancy Outcome (HAPO) study involving 15 multinational centers reported the prevalence of GDM between 9.3 and 25.5% in the global population (Sacks et al, 2012). GDM has become a major health burden, as it is associated with poor fetal-maternal outcomes, including polyhydramnios, higher cesarean section rate, preeclampsia, shoulder dystocia, and macrosomia (Beucher et al, 2010;Ismail et al, 2011;Catalano et al, 2012;Kc et al, 2015). Furthermore, Ehrlich et al (2011) reported an increased risk of GDM by 38% in future pregnancies in women diagnosed with GDM during their first pregnancies compared to only 3.5% in women without GDM.…”
Section: Introductionmentioning
confidence: 99%